ASSESSMENT OF AVAILABILITY, ACCESSIBILITY AND UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY RESOURCES IN CONTENT DELIVERY AMONG LECTURERS IN FEDERAL COLLEGES OF EDUCATION IN NIGERIA - Zubairu, Suleiman Abubakar; Tukur, Abdullahi K. (Sokoto Educational Review, 2015)
This paper aimed at assessing the availability, accessibility and utilization of Information and Communication Technology (ICT) resources in content delivery among lecturers of FCEs in Nigeria. Three research questions were drawn to guide the study. A Survey research design was adopted in conducing the study. The population of the study comprises of all the lecturers in Federal Colleges of Education in Nigeria. They are five thousand and seventy one (5,071) in number. A sample size of eight hundred and forty three (843) lecturers was used for the study. They were selected using cluster, simple random and proportional sampling techniques. A modified questionnaire tagged Teachers ICT usage survey from the ICT Survey Indicator for teachers and staff developed by both UNESCO (2004) and the New Zealand Ministry of Education (MINEDU) (1999) was used for data collection. Frequency count was used to answer research questions. The findings of this study revealed that ICT resources are not available in Federal Colleges of Education in Nigeria. It was also revealed that ICT resources which were supposed to be used in content delivery in FCE were not accessible. This study recommends, among others, that the Government, NCCE and the managements of FCE should join hands to ensure that computer laboratories are available in FCE in Nigeria with adequate functional computer hardware and software and functional internet facilities that will enhance the standard of content delivery.